DISIPLIN KERJA DAN KOMPENSASI DALAM MEMPENGARUHI KINERJA PADA PT PNM MEKAAR KABUPATEN SITUBONDO DENGAN MEDIASI VARIABEL KEPUASAN KERJA - Safira, Gilda Nindita; Sari, Lita Permata; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The study aimsto determine the influence of Work Discipline and Compensation on Performance at PT PNM Mekaar in the Situbondo Regency with the Mediationof Job Satisfaction Variables. The sampling technique in this research is a Saturated Sample. This study's data analysis and hypothesis testing utilize Partial Least Square (PLS-SEM). The results of hypothesis testing for direct effects using Smart PLS 3.0 application indicate that work discipline has a positive and significant influence on job satisfaction,compensation has a positive and significant influence on job satisfaction, work discipline has a positive and significant influence on employee performance, compensation has a negative yet significant influence on employee performance, job satisfaction has a positive and significant influence on employee performance, work discipline has a positive but not significant influence on employee performance through job satisfaction, and compensation has a positive and significant influence on employee performance through job satisfaction.